REVITALISASI FUNGSI MASJID SESUAI ZAMAN RASULULLAH MELALUI IMPLEMENTASI PSAK 45: STUDI EMPIRIS PADA MASJID A DAN B - Marsdenia - (Conference In Business, Accounting, And Management (CBAM), 2015)
This research explores how PSAK 45 practices in Mosque Organization facilitates a revitalization mosque role as Rasulullah Era. This research is a case study in two different mosque, Entity A and B.  Mosque A organized under famous community moslem A. Mosque B location in one of famous town house in City X. Research metodology is qualitatif approach which is use also quantitatif data and also field observation and in dept interview with  stakeholder. There are  some findings: first,the daily activities of  both  mosque have  some activities similar to Rasululloh era such as: Mosque as education center, distribution of Zakat, Infaq, Sadaqoh, and so many others,, second, Each Mosque have very simple accounting record for those activities third, there are some activities in Rasululloh era that unusual for current condition such as health activities, social meeting, others, fourth, Implementation of PSAK 45 very limitation, since no accrual basis, only very simple cash basis and simple financial reporting such as simple cash flow report.  Keywords: PSAK 45, Mosque, Non for Profit, Public Entity, Accounting